Building a framework for ergonomic research on laparoscopic instrument handles. (June 2016) - Li, Zheng; Wang, Guohui; Tan, Juan; Sun, Xulong; Lin, Hao; Zhu, Shaihong
Abstract: Laparoscopic surgery carries the advantage of minimal invasiveness, but ergonomic design of the instruments used has progressed slowly. Previous studies have demonstrated that the handle of laparoscopic instruments is vital for both surgical performance and surgeon's health. This review provides an overview of the sub-discipline of handle ergonomics, including an evaluation framework, objective and subjective assessment systems, data collection and statistical analyses. Furthermore, a framework for ergonomic research on laparoscopic instrument handles is proposed to standardize work on instrument design. Highlights: Laparoscopic instrument handles need ergonomic design for comfortable. The methodology in ergonomic study on laparoscopic instrument handles is elaborated. A guideline is feasible for ergonomic evaluation of laparoscopic instrument handles.